Effects of Prenatal Pulsed Electromagnetic Field and 27.12-Megahertz Radiofrequency Exposure on Fetal Development and Placental Stress Response in Rats - Gülüm Ceren Bozlu; Mekin Sezik; Rümeysa Taner; Halil Asci; Adem Milletsever; Ozlem Ozmen; Havva Serap Toru Ateser; Selçuk Cömlekci (Journal of Fetal Medicine, 2026)
Abstract Pulsed electromagnetic field (PEMF) and radiofrequency electromagnetic field (RF-EMF) stimulation promote neovascularization and angiogenesis and may have therapeutic potential for preventing or treating early-onset fetal growth restriction. We investigated the morphological and histopathological effects of PEMF and RF-EMF, administered separately or in combination, during early (gestational days 0–10) and late (days 10–20) pregnancy in a rat model. Thirty-two pregnant Wistar albino rats were randomly assigned to eight experimental groups. Animals were exposed to PEMF, RF-EMF, or combined EMF protocols during either early or late gestation. Fetal biometric measurements at term, histopathological examination of fetal organs, and placental heat shock protein 70 (HSP-70) immunostaining were evaluated. Histopathological examination demonstrated normal brain, lung, liver, heart, intestine, and kidney tissues in all fetuses except for intracranial hemorrhage foci detected in two fetuses exposed to combined EMF treatment. Fetal weight-standardized head-crown length and biparietal diameter were significantly greater in fetuses exposed to RF-EMF during early pregnancy than in the other groups. Placental weights were similar among groups. Intense HSP-70 immunostaining was observed in placentas exposed to PEMF and RF-EMF during the first 10 days of gestation. No external malformations or skeletal abnormalities were identified. At the exposure parameters used, PEMF and RF-EMF were not associated with significant teratogenic effects and appeared relatively safe for fetal development. Increased fetal growth despite unchanged placental weight may reflect enhanced uteroplacental perfusion or adaptive placental stress responses. However, the potential adverse effects of combined EMF exposure on the fetal brain warrant further investigation. Carefully controlled exposure to PEMF or RF-EMF during pregnancy may be a relatively safe and nonteratogenic approach that could enhance fetal growth, but combined EMF modalities should not be used until potential fetal brain effects are better understood.